Health effects of energy drinks on children, adolescents, and young adults - Kawałko, Kinga; Rynio, Grzegorz; Pondel, Kamil; Karaś, Anna; Bielewicz, Krzysztof (Journal of Education, Health and Sport, 2022)
Energy drinks are very popular nowadays. The number of people consuming this type of drink is growing every year, not only in the adult group but also in the population of adolescents and children. For many people, they are an alternative to stimulating coffee. In addition to the desired effects such as reducing fatigue, improving concentration and increasing physical and mental performance, energy drinks can also have adverse effects. The substances they contain, such as caffeine, taurine and large amounts of carbohydrates, may contribute to an increased risk of cardiovascular complications, metabolic and gastroenterological diseases, and mental disorders. [1] The aim of the article is to present the negative effects of consuming energy drinks in the population of adolescents and children.